An investigation of the effect of tensile stress on the permeability characteristics and opening sizes of geotextiles - Addis, Philip Charles (My University, 2016)
A series of tests were carried out on three types of geotextiles to investigate the effects of biaxial tensile loading on their permeability and filtration opening sizes. A woven slit-film and two nonwoven needle punched geotextiles were tensioned either equally in both directions or unequally, The tensile forces exerted were small. less than 10% of the geotextiles' tensile strength. And a tensile loading frame was designed for this purpose. An attempt to measure the effect on the permeability was made using a large diameter permeamcter that was subjected to un upward water now. A hydrodynamic sieving'- mechanism HSM) was used to investigate the effect on the opening sizes of the geotextiles. Certain aspects of the hydrodynamic test method were also investigated.